2018
DOI: 10.3390/jcdd5020024
|View full text |Cite
|
Sign up to set email alerts
|

Some Isolated Cardiac Malformations Can Be Related to Laterality Defects

Abstract: Human beings are characterized by a left–right asymmetric arrangement of their internal organs, and the heart is the first organ to break symmetry in the developing embryo. Aberrations in normal left–right axis determination during embryogenesis lead to a wide spectrum of abnormal internal laterality phenotypes, including situs inversus and heterotaxy. In more than 90% of instances, the latter condition is accompanied by complex and severe cardiovascular malformations. Atrioventricular canal defect and transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 178 publications
(217 reference statements)
0
19
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11] Recently, new hypotheses have been proposed on the development of atrial septum based on the experimental data. 12,13 Goddeeris et al 12 used a genetic marker and novel magnetic resonance microscopy technique to demonstrate the origins of the dorsal mesenchymal protrusion in the dorsal mesocardium, and its valuable contribution to atrioventricular septation. They showed that sonic hedgehog signalling is required within the dorsal mesocardium for its contribution to the atria.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Recently, new hypotheses have been proposed on the development of atrial septum based on the experimental data. 12,13 Goddeeris et al 12 used a genetic marker and novel magnetic resonance microscopy technique to demonstrate the origins of the dorsal mesenchymal protrusion in the dorsal mesocardium, and its valuable contribution to atrioventricular septation. They showed that sonic hedgehog signalling is required within the dorsal mesocardium for its contribution to the atria.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that mutations in cilia genes are also involved in isolated CHD-especially AVSDs and D-transposition of the great arteries (D-TGA) (Versacci et al 2018). In patients with CHD but no HTX, there is a high incidence of ciliary motion defects-up to 51% in one study (Garrod et al 2014).…”
Section: Heterotaxy and Ciliopathiesmentioning
confidence: 99%
“…Abnormal ciliary structure or function is associated with syndromic ciliopathies which include primary ciliary dyskinesia (PCD) and HTX, both of which are associated with CHD (Sutherland & Ware, ). However, there is evidence that mutations in cilia genes are also involved in isolated CHD, especially atrioventricular septal defects and D‐TGA (Versacci et al, ). In patients with CHD but no HTX, there is a high incidence of ciliary motion defects, up to 51% in one study (Garrod et al, ).…”
Section: Monogenic Causes Of Isolated Chdmentioning
confidence: 99%
“…However, there is evidence that mutations in cilia genes are also involved in isolated CHD, especially atrioventricular septal defects and D-TGA (Versacci et al, 2018). In patients with CHD but no HTX, there is a high incidence of ciliary motion defects, up to 51% in one study (Garrod et al, 2014).…”
Section: Heterotaxy and Ciliopathiesmentioning
confidence: 99%